1997
DOI: 10.1007/bf02783306
|View full text |Cite
|
Sign up to set email alerts
|

Lead disrupts eicosanoid metabolism, macrophage function, and disease resistance in birds

Abstract: Lead (Pb) affects elements of humoral and cell-mediated immunity, and diminishes host resistance to infectious disease. Evidence is presented supporting a hypothesis of Pb-induced immunosuppression stemming from altered fatty acid metabolism, and mediated by eicosanoids and macrophages (MO). Chronic Pb exposure increases the proportion of arachidonate (ArA) among fatty acids in lipid from avian tissues, and this change provides precursors for eicosanoids, the oxygenated derivatives of ArA that mediate MO acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Macrophage phagocytosis is one of the first lines of defense against pathogens, and it also is important for antigen presentation and subsequent antibody production. Impaired phagocytic ability increases susceptibility to bacterial and parasitic infection [30], and macrophage phagocytosis has been used to assess immunological response to contaminant exposure in wildlife populations [14,53]. Albatross macrophages from cryopreserved peripheral WBCs responded well in our phagocytosis measurements; 76% of macrophages ingested yeast, with the number of yeast particles that macrophages ingested varying across the categories recorded (% macrophages that ingested 1–2 yeast, 33% ± 5%; 3–4 yeast, 18% ± 5%; 5–10 yeast, 20% ± 7%; gt;10 yeast, 5% ± 4%).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage phagocytosis is one of the first lines of defense against pathogens, and it also is important for antigen presentation and subsequent antibody production. Impaired phagocytic ability increases susceptibility to bacterial and parasitic infection [30], and macrophage phagocytosis has been used to assess immunological response to contaminant exposure in wildlife populations [14,53]. Albatross macrophages from cryopreserved peripheral WBCs responded well in our phagocytosis measurements; 76% of macrophages ingested yeast, with the number of yeast particles that macrophages ingested varying across the categories recorded (% macrophages that ingested 1–2 yeast, 33% ± 5%; 3–4 yeast, 18% ± 5%; 5–10 yeast, 20% ± 7%; gt;10 yeast, 5% ± 4%).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments with bovine macrophages treated with 10 −4 M Pb showed no impairment in the ability to phagocytize latex beads, but treatment with cadmium and mercury did result in a decrease in phagocytosis by these cells . In contrast, phagocytosis of sheep erythrocytes by peritoneal macrophages isolated from turkey poults, treated with 100 ppm Pb acetate‐trihydrate in their feed, was 50% less than controls and sheep erythrocytes phagocytized per macrophage was 25% less than controls . Impaired phagocytosis of opsonized chicken erythrocytes was observed for rabbit‐derived alveolar macrophages treated with 10 −5 M Pb in culture .…”
Section: Pb Effect On Chemotaxis and Phagocytosismentioning
confidence: 95%
“…However, results showed that macrophage function (required to phagocytose circulating Salmonella bacteria) was reduced by lead due to alterations in the phospholipid cell membrane, inducing membrane fragility and loss of integrity. Knowles and Donaldson (1997) also recorded a severalfold increase in secretion of prostaglandins (PGF 2α and PGE 2α ) from macrophages as a result of lead exposure. Prostaglandins secreted by macrophages control the function of other cells in the immune system.…”
Section: Metalsmentioning
confidence: 97%
“…Antibody production to SRBCs, as measured by the splenic plaque-forming cell assay, also was decreased in lead-dosed birds. On the other hand, upland game birds, including Japanese quail (Coturnix coturnix japonica), turkey poults (Melagris gallaparvo), and chickens (Gallus gallus domesticus), treated with lead acetate in either diets or water, demonstrated little immune responsiveness (Fair & Ricklefs, 2002;Grasman & Scanlon, 1995;Morgan et al, 1975;Lee et al, 2001;Knowles & Donaldson, 1997). Morgan et al (1975) saw no effect on SRBC titers in Japanese quail, and Fair and Ricklefs (2002) also showed no response to challenge with chukar (Alectoris graeca) RBCs or to a nonvirulent strain of Newcastle disease virus.…”
Section: Metalsmentioning
confidence: 98%
See 1 more Smart Citation